2006
DOI: 10.1098/rspb.2006.3633
|View full text |Cite
|
Sign up to set email alerts
|

Rates of nausea and vomiting in pregnancy and dietary characteristics across populations

Abstract: Nausea and vomiting in pregnancy (NVP) is a pervasive and debilitating phenomenon in humans. Several adaptive explanations for NVP occurrence have been recently proposed, the two most prominent of which predict associations with nutritional intake or specific dietary components. Here we extend previous crosscultural analyses by analysing associations between NVP prevalence in 56 studies (21 countries) and quantitative estimates of per capita intake across major dietary categories, measured for the year of stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 26 publications
2
41
1
1
Order By: Relevance
“…Three previous studies examined the effects of NVP on food intake using cross‐sectional data, two in Scandinavia (Latva‐Pukkila et al, 2010; Chortatos et al, 2013) and one ecological study based on international data (Pepper & Craig Roberts, 2006). There is little consistency in the findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three previous studies examined the effects of NVP on food intake using cross‐sectional data, two in Scandinavia (Latva‐Pukkila et al, 2010; Chortatos et al, 2013) and one ecological study based on international data (Pepper & Craig Roberts, 2006). There is little consistency in the findings.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that NVP confers functional advantages by preventing intake of substances that may be harmful to the mother or fetus (Flaxman & Sherman, 2000; Pepper & Craig Roberts, 2006) (the maternal and embryo protection hypothesis), or by decreasing nutrient intake thereby stimulating placental growth (Huxley, 2000) (the placental growth and development hypothesis). This latter hypothesis is based on the assumption of a reduction in appetite and overall energy intake resulting from NVP which may be supported by the current study in which severely nauseous women reduced their energy intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, adaptations of this type appear not only to be dependent on the period in which the mother's diet is altered but also the diet to which she is rehabilitated (7) . One fundamental consideration is that the self-limitation in food intake between early-to-mid gestation that occurs commonly as a result of the nausea affecting approximately 90% of pregnant women in the UK may be directly linked to Western diets (8) . The extent to which this factor relates to changes in placental function and/or fetal growth remains less clear, but there is a need to match global preand postnatal nutritional requirements in order to avoid accelerated growth and the concomitant increased risk of later obesity and metabolic complications (9) .…”
mentioning
confidence: 99%
“…In the present study we found that carbohydrate-rich foods such as breads and cereals, sugared soft-drinks, and biscuits were foods the NVP women had high odds of eating more of. That women suffering from NVP increase their intake of bread, biscuits, and sweet sugar-containing foods during pregnancy, as well as total carbohydrates, has been * Number (%) of women with outcome ** Adjusted for total energy intake observed by others (2,5,12,18). Elsewhere it has been found that a diet high in carbohydrates may aggravate gastric dysrhythmias when compared to high protein diets, which can lead to nausea, suggesting that women suffering NVP may potentially be exasperating their condition by virtue of their dietary choices (19).…”
Section: Discussionmentioning
confidence: 99%